Emotional intelligence and state - trait anxiety in future teachers - Carrillo Salazar, Blanca Cecilia (2016)
The following investigation has as its main objetive the description of the relationship that exists between Emotional Intelligence and the degree of the State – Trait of Anxiety; for this a descriptive and correlational investigation was carried out. The participants were 166 individuals between 16 and 26 years of age in an Institute of Higher Learning in Lima, Perú. A Bar-On Emotional Quotient Inventory and Spielberg’s State - Trait Anxiety Inventory were applied. The results found the existence of a highly significant relationship between the Total Emotional Intelligence and the level of State - Trait Anxiety Inventory. According to the Emotional Intelligence component it was found that 81% of the participants presented an adequate level of Emotional Intelligence and with respect to the State - Trait Anxiety Inventory it was found that around 81% had a low level of anxiety. In conclusion, the hypothesis was deemed affirmative.